2020
DOI: 10.1186/s41824-020-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-site 123I-FP-CIT reference values from individuals with non-degenerative parkinsonism—comparison with values from healthy volunteers

Abstract: Iodine 123-radiolabeled 2β-carbomethoxy-3β-(4-iodophenyl)-N-(3-fluoropropyl) nortropane (123 I-FP-CIT) SPECT can be performed to distinguish degenerative forms of movement disorders/parkinsonism/tremor from other entities such as idiopathic tremor or drug-induced parkinsonism. For equivocal cases, semi-quantification and comparison to reference values are a necessary addition to visual interpretation of 123 I-FP-CIT scans. To overcome the challenges of multi-center recruitment and scanning of healthy volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Furthermore, the SSRI treatment led to statistically significantly lower binding ratios in SERT-rich brain areas (Booij et al, 2007). SERT and DAT have been shown to be distributed differently among brain regions (de Win et al, 2005; Fahmi et al, 2020). SERT binding potential in unmedicated patients seems to be reduced, especially in more severely affected individuals with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the SSRI treatment led to statistically significantly lower binding ratios in SERT-rich brain areas (Booij et al, 2007). SERT and DAT have been shown to be distributed differently among brain regions (de Win et al, 2005; Fahmi et al, 2020). SERT binding potential in unmedicated patients seems to be reduced, especially in more severely affected individuals with depression.…”
Section: Discussionmentioning
confidence: 99%
“…The SBR asymmetry index that was used in previous studies (asymmetry index by method 1) was calculated as the absolute ratio of difference to average striatal SBRs ( 7 , 11 16 ). Although there was a significant decrease in the putaminal asymmetry index using method 1 after the 1-year follow-up mark, there was no notable pattern of changes during the entire follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported higher SBRs in females of NCs ( 24 , 25 ), while others reported no difference according to gender ( 26 , 27 ). Furthermore, this gender related difference of SBRs were suggested to be dependent on the image reconstruction method ( 11 , 28 ). Further studies with an age- and gender-matched comparison with a larger number of NCs may be needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential limitation of the use of these databases is the additional instrumental variance in SBR values caused by the heterogeneity in equipment, despite the inter-center (inter-system) calibration, which could reduce their sensitivity [ 9 , 10 ] . Alternatively, SBR reference values are obtained locally and retrospectively from normal 123 I-FP-CIT routine examinations of a patient group presenting heterogeneous suspected diagnoses, but without dopaminergic neurodegenerative pathology, after a follow-up period lasting up to 5 years [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%